Correlation of Anti-Müllerian Hormone with Polycystic Ovarian Disease and its Relation with Age - Omer Muhammed, Sara; Najmaddin Fattah, Chro (Kurdistan Journal of Applied Research, 2019)
Polycystic ovarian disease (PCOD) is a common endocrine disorder of reproductive-aged women. Serum Anti-Müllerian hormone (AMH) increases in PCOD women due to increased follicle numbers. Objectives: The aim was to evaluate ovarian reserve by measuring level of AMH among PCOD women. Prospective cohort study was performed on 62 ladies who aged 25 to 40 years and diagnosed by Rotterdam criteria as PCOD in Sulaimani Maternity Teaching Hospital/Outpatient Gynecological Clinic during May 2018 to May 2019. Consents were obtained from patients for their inclusion. Inclusion criteria were age of 25-40 years and diagnosis of PCOD. The patients’ ages, body mass index (BMI) and level of AMH were recorded. Sample size estimation was performed by "GPower 3.1" and "IBM SPSS Statistics version 25" was used for analysis of data. P-value of (?0.05) was considered significant. The mean±SD (standard deviation) of age of women were 31.7±5 years. The majority of participants were housewives from inside of Sulaimani City and most of them were diagnosed to have PCOD through clinical features and results of ultrasonography. The mean±SD of BMI and AMH were 26.2±2.8 kg/m2 (ranged from 21.3 to 33.2 kg/m2) and 4.76±3.51 ng/ml (ranged from 0.1-14.6 ng/ml) respectively. There was significant association between age of the participants and AMH and the association of BMI and AMH was not significant. The level of AMH is decreased with aging and it is higher among PCOD women due to increased follicle numbers. The level of AMH was not associated with BMI.